A New Perspective on Visual Word Processing Efficiency - Houpt, Joseph W. (2013)
As a fundamental part of our daily lives, visual word processing has received much attention in the psychological literature. Despite the well established advantage of perceiving letters in a word or in a pseudoword over letters alone or in random sequences using accuracy, a comparable effect using response times has been elusive. Some researchers continue to question whether the advantage due to word context is perceptual. We use the capacity coefficient, a well established, response time based measure of efficiency to provide evidence of word processing as a particularly efficient perceptual process to complement those results from the accuracy domain.